The ghost in the attic - Butler, Dori Hillestad (Butler, Dori Hillestad. Haunted library, 2014)
"When a neighbor calls about ghostly noises in her attic, Kaz and Claire agree to investigate. Could that very familiar-looking ghost dog Kaz sees through the attic window be his lost dog, Cosmo? Venturing outside could be dangerous, but Kaz has to find a way to be reunited with Cosmo before he loses him for good."--